Outcomes related to IGFBP-7 in patients with heart failure and reduced ejection fraction and effects of dapagliflozin: findings from DAPA-HF. (3rd October 2022) - Adamson, C; Welsh, P; Morrow, D A; Docherty, K F; Hammarstedt, A; Inzucchi, S E; Kober, L; Kosiborod, M N; Martinez, F A; Ponikowski, P; Sabatine, M S; Solomon, S D; et al.
Abstract: Introduction: Insulin-like growth factor binding protein 7 (IGFBP-7) has been proposed as a novel prognostic biomarker in heart failure, but the association between IGFBP-7 and cardiovascular outcomes has not been examined in a large cohort of patients with heart failure and reduced ejection fraction (HFrEF). Purpose: In this post-hoc analysis of the Dapagliflozin And Prevention of Adverse outcomes in Heart Failure trial (DAPA-HF) we examined the relationship between plasma IGFBP-7 level and outcomes in patients with HFrEF, the effect of dapagliflozin according to IGFBP-7 level and change in IGFBP-7 at 12 months. Methods: Patients in NYHA class II–IV with LVEF ≤40% and elevated NT-proBNP were included in DAPA-HF. Participants were randomly allocated to dapagliflozin 10mg or matching placebo. In this analysis, patients were categorized by IGFBP-7 tertile. The primary outcome was a composite of cardiovascular death or worsening HF event; secondary outcomes were components of the primary outcome and all-cause mortality. The risk of each outcome was compared across thirds of IGFBP-7 using Cox regression models with adjustment for NT-proBNP and high-sensitivity troponin T as well as: randomised treatment, age, sex, race, region, systolic blood pressure, heart rate, ejection fraction, estimated glomerular filtration rate, NYHA class, history of HF hospitalisation, ischaemic aetiology of HF, hypertension, stroke, atrial fibrillation, prior MI and stratified by diabetes status. The efficacy of dapagliflozin was assessed according to baseline IGFBP-7 level. Change in IGFBP-7 at 12 months was assessed using the ratio of geometric means. Results: 3158 patients had measurement of IGFBP-7 at baseline. The median value of IGFBP-7 was 192 ng/mL (interquartile range 158–246). Patients in the highest third of IGFBP-7 levels had more advanced HF, with higher NYHA class and NT-proBNP, had worse renal function and more type 2 diabetes. Patients in the highest third had the highest rate of the primary outcome (Figure 1). The adjusted hazard ratio (aHR) for the primary endpoint (with lowest third of IGFBP-7 as reference) was 0.94 (95% CI 0.74–1.20) for middle third and 1.49 (95% CI 1.17–1.89) for top third. The corresponding aHRs for worsening HF event were 0.99 (95% CI 0.72–1.36) for middle third and 1.84 (95% CI 1.35–2.50) for top third. Cardiovascular and all-cause mortality did not vary by IGFBP-7 tertile. The benefit of dapagliflozin was consistent regardless of baseline IGFBP-7 (p for interaction for primary endpoint = 0.34). The change in IGFBP-7 from baseline to 12 months did not differ between placebo and dapagliflozin. Conclusions: Elevation of IGFBP-7 in patients with HFrEF was associated with more adverse HF outcomes, even after adjustment for both NT-proBNP and hsTnT. The treatment benefit of dapagliflozin did not vary by baseline IGFBP-7. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The DAPA-HF trial was funded by AstraZeneca.CA and JJVM are supported by a British Heart Foundation Centre of Research Excellence Grant.